Promoting 'Design Of Experiment' Techniques To Manufacturing Industry In Malaysia Via The World Wide Web. - Abdul Aziz, Zalina (2003)
Acceptance of the usefulness of modem statistical methods in quality improvement initiatives is growing among engineering and management personnel in the manufacturing industry in Malaysia and elsewhere. Among the contributing factors are the use of quality as a competitive instrument and the introduction of the ISO 9000 Quality Management Systems by the International Organization for Standardization.